Seasonal Prevalence and Phenomenal Biology as Tools for Dengue Mosquito Aedes aegypti (Linnaeus) (Diptera: Culicidae) Management - Sarwar,Muhammad (2022)
Abstract Vector monitoring is a fundamental tool for mosquito control activities and assembles information on the relative population size, species composition and advantages in dengue disease prevention. Investigations have been initiated for the exploration of relative abundance and biology of the dengue vector Aedes aegypti (Linnaeus) mosquito to provide baseline information for effective vector control and dengue prevention strategies. The studies were conducted for two years (2018-2019) from January to December focusing on the developmental stages of mosquitoes. The results revealed that seasonal densities of Ae. Aegypti undergoes considerable variations throughout the year. The population dynamics of the vector exhibited well-defined increasing populations during the post-monsoon season. Consequently, observations found a rapid decline in its abundance during the months of December to February until it reached the next peak in March and April. Datasets exhibited that the vector population gradually decreased to a lower level from May to June and there was a population increase in July and August of the years. The developmental stages of Ae. aegypti (egg to adult) revealed that three days after the female mosquitoes had taken blood food of Balb/C mouse began to lay eggs. The egg stage lasted for 3 days and after hatching, the four larval instars; first, second, third and fourth earmarked about 1.3, 1.1, 1.2 and 2.4 days, respectively to develop into pupae. The pupal stage developed into adults in 2 days. The entire life cycle was completed within about 11 days including female longevity 28 and male longevity 21 days, respectively.